2011
DOI: 10.3390/ijerph8010234
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Variation in Price Minimizing Behaviors: Findings from the International Tobacco Control (ITC) Four Country Survey

Abstract: This paper examines how socio-economic status (SES) modifies how smokers adjust to changes in the price of tobacco products through utilization of multiple price minimizing techniques. Data come from the International Tobacco Control Policy Evaluation (ITC) Four Country Survey, nationally representative samples of adult smokers and includes respondents from Canada, the United States, the United Kingdom and Australia. Cross-sectional analyses were completed among 8,243 respondents (7,038 current smokers) from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 28 publications
4
80
0
1
Order By: Relevance
“…Overall, white, female, older and more addicted smokers were more likely to purchase cigarettes in high quantities and try to avoid taxes. The fact that female smokers were more likely to purchase in high quantities and try to avoid taxes is consistent with the study by Licht et al, 8 which uses ITC data from four countries. As well, studies using non-ITC data have found that female smokers were more likely to purchase in ‘less expensive venues’ or from Indian reservations, and also that female smokers were more likely to use promotional offers ‘every time they see one’ 20–22.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, white, female, older and more addicted smokers were more likely to purchase cigarettes in high quantities and try to avoid taxes. The fact that female smokers were more likely to purchase in high quantities and try to avoid taxes is consistent with the study by Licht et al, 8 which uses ITC data from four countries. As well, studies using non-ITC data have found that female smokers were more likely to purchase in ‘less expensive venues’ or from Indian reservations, and also that female smokers were more likely to use promotional offers ‘every time they see one’ 20–22.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies from the ITC Project have examined price-minimising behaviours in relationship to smoking cessation and smoker socioeconomic status using data from the USA, the UK, Canada and Australia 6 8. The present study examines trends in purchasing patterns in a group of US adult smokers surveyed annually between 2002 and 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The cigarette consumption weight was used to obtain the average price per pack, because evidence from selected states shows that the use of priceminimization strategies was related closely to smoker's cigarette consumption, meaning heavy or more-addicted smokers were more likely to use these strategies. [11][12][13][14][15] In other words, self-reported cigarette prices in the NATS may differ depending on smoker's cigarette consumption.…”
Section: Methodsmentioning
confidence: 99%
“…5 Strategies smokers use to minimize their cigarette costs include crossing borders to purchase cigarettes in states with lower excise taxes; purchasing lower-priced cigarettes from retailers on the Internet or on Indian reservations; purchasing cigarettes on the black market; rolling their own cigarettes; switching to a less expensive or generic brand; using price-related discounts such as coupons or multi-pack offers; and purchasing cartons instead of packs. [5][6][7][8][9][10][11][12][13][14] Using the 2009-2010 National Adult Tobacco Survey (NATS), the main purpose of the current analysis is to evaluate the prevalence of adult smokers who used one or more of five common price-minimization strategies in the previous year, and per-pack price reductions associated with use of these strategies at both the national and state level. The national prevalence also is stratified by type of strategies and by smokers' cigarette consumption level.…”
Section: Introductionmentioning
confidence: 99%
“…15 Evidence suggests that purchasing decisions may also vary by race and ethnicity, with non-Hispanic whites being more likely to purchase cartons than packs, and black smokers most likely to use mentholated cigarettes. 13,14,[16][17][18] On the other hand, studies of the advertised prices of cigarettes show that they are cheaper in neighborhoods with more African Americans and low income residents. [19][20][21] As a result, they have access to cheaper cigarettes and may pay less than other groups.…”
Section: Introductionmentioning
confidence: 99%